Large platelets but not putative endothelial progenitor cells are associated with low strut coverage after drug-eluting stent implantation. (15th November 2015) - Nührenberg, Thomas G.; Zhao, Min; Stratz, Christian; Amann, Michael; Valina, Christian M.; Gick, Michael; Trenk, Dietmar; Binder, Harald; Büttner, Heinz Joachim; Neumann, Franz-Josef
Abstract: Objectives: : This study assessed whether different subsets of circulating endothelial and putative endothelial progenitor cells (CEC and EPC) correlate with stent strut coverage (SSC) using second generation optical coherence tomography (OCT). Background: : Due to the lack of imaging modalities with a resolution down to the magnitude of a few cells, the influence of EPC on endothelialisation of drug-eluting stents has not been assessed in patients. Methods: : In 37 patients, SSC of everolimus-eluting stents was assessed by OCT 5–7 months after stent implantation. Different subsets of EPC (CD34 + KDR +, CD34 + KDR + CD45 dim, CD133 +, CD3 + CD31 + ), CEC (CD31 + CD45 − CD146 + ), and CD31 + CD45 − CD146 − representing large platelets were analysed by flow cytometry, including viability analyses with 7-AAD. Statistical analysis comprised univariate regression analysis and multivariable models integrating OCT and flow cytometry data as well as clinical variables. Results: : SSC and frequency of different cell types were highly comparable with previously published data. EPC defined in part by KDR expression were mostly non-viable. On univariate and in multivariable models, no association between EPC counts and strut coverage was detected. For CD31 + CD45 − CD146 − counts, representing large platelets, an inverse relationship with strut coverage was identified by a multivariable regression model adjusting for age, sex, diabetes mellitus, NYHA and CCS class, CRP, serum triglycerides, glucose and creatinine (beta = − 9.42, p = 0.006). Conclusions: : There was no significant association between EPC or CEC and healing after drug-eluting stent implantation. Yet, CD31 + CD45 − CD146 − cells were associated with low SSC. These data suggest that large platelets may represent a more important mediator of late stent endothelialisation than EPC.